2006
DOI: 10.1136/gut.2005.080739
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics prevent bacterial translocation and improve intestinal barrier function in rats following chronic psychological stress

Abstract: Background and aim: Chronic psychological stress, including water avoidance stress (WAS), induces intestinal mucosal barrier dysfunction and impairs mucosal defences against luminal bacteria. The aim of this study was to determine the ability of a defined probiotic regimen to prevent WAS induced intestinal pathophysiology. Methods: Male rats were subjected to either WAS or sham stress for one hour per day for 10 consecutive days. Additional animals received seven days of Lactobacillus helveticus and L rhamnosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
221
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(234 citation statements)
references
References 28 publications
3
221
3
7
Order By: Relevance
“…Pathological bacterial translocation as a marker of impaired barrier function can also be effectively reduced by probiotic therapy. [27][28][29][30] In conclusion, oral administration of heat-killed b240 was found to reduce S. Typhimurium infection effectively through inhibition of S. Typhimurium adhesion and invasion of intestinal epithelial cells, which normally leads to systemic infection associated with multiple organ failure. Heat-killed b240 thus appears to play a valuable role in preventing the lethality of S. Typhimurium infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological bacterial translocation as a marker of impaired barrier function can also be effectively reduced by probiotic therapy. [27][28][29][30] In conclusion, oral administration of heat-killed b240 was found to reduce S. Typhimurium infection effectively through inhibition of S. Typhimurium adhesion and invasion of intestinal epithelial cells, which normally leads to systemic infection associated with multiple organ failure. Heat-killed b240 thus appears to play a valuable role in preventing the lethality of S. Typhimurium infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Others have anti-inflammatory effects 26 or enhance the mucosal defense against luminal bacteria by preventing bacterial adherence to the epithelial cell surface, eliminating bacterial translocation and decreasing the increased intestinal permeability. 27 Rousseaux et al 22 reported that Lactobacillus NCFM induced, through the NF-κB pathway, MOR1 and CB2 expression, which contributed to the modulation and restoration of the normal perception of visceral pain. Sinn et al 9 demonstrated reduction of abdominal pain or discomfort among patients receiving a daily dose of 2×10 9 cfu of L. acidophilus-SDC 2012,2013 over four weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some probiotic studies in humans have reported a decrease in intestinal permeability (36,38), whereas others have been negative or inconclusive (11,24), suggesting that this activity may depend on the probiotic strain and species as well as the target population and its resilience capacity of the intestinal mucosa. Evidence for probiotic effects on barrier function has also been demonstrated in rat models of chronic stress, hemorrhagic shock, and sepsis although the mechanisms have not been elucidated (32,47). Recently, the probiotic Escherichia coli (E. coli) Nissle 1917 was shown to inhibit a leaky gut by upregulation of ZO-1 expression in murine intestinal epithelial cells and to confer protection from dextran sodium sulfate (DSS)-induced colitis (41,48).…”
Section: Translational Highlights This Study Demonstrates That In Thmentioning
confidence: 99%